Students’ Speaking Ability under the Use of Interactive E-Module In Fourth Semester Students of English Education Study Program at Muhammadiyah Kotabumi University Academic Year 2021/2022 - Angelica Marsellia; Elis Susanti; Rulik Setiani; Mei Lastri Parhusip; M. Nur Wahid; Laily Syafitri; Tiara Gian Safindra (Edukasi Lingua Sastra, 2023)
The researcher was interested in carrying out a research entitled; Students’ Speaking Ability under the Use of Interactive E-Module in Fourth Semester Students of English Education Study Program at Muhammadiyah Kotabumi University Academic Year 2021/2022. The research was aimed to describe what is the level of students’ speaking ability under the use of Interactive E-Module in fourth semester students of English Education study program at Muhammadiyah Kotabumi University academic year 2021/2022. This research was done at fourth semester students of English Education study program at Muhammadiyah Kotabumi University. The method of this research was descriptive quantitative. The sample were 44 students. The researcher used total sampling technique to select the sample. In collecting the data, the researcher used speaking test in form of retelling short movie. Furthermore, students would be assessed by two raters using a speaking assessment component that contains aspects of speaking such as: pronunciation, vocabulary, grammar, fluency, and comprehension. In analyzing the data, researcher used descriptive statistics and tendency data. From the analysis, it could be concluded that the students’ speaking ability under the use of Interactive E-Module in fourth semester students of English Education study program was Good. The most dominant score level obtained by the students which 45% was categorized to Good. Interactive E-Module also made students more active and motivated during the speaking learning.